2019
DOI: 10.1007/s11420-019-09690-2
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Epidural Hematoma after Elective Posterior Lumbar Decompression: Incidence, Timing, Risk Factors, and Associated Complications

Abstract: Background: Symptomatic post-operative lumbar epidural hematoma (PLEH) is a complication of lumbar spine surgery that can cause permanent neurologic consequences through compression of the cauda equina and nerve roots. Questions/Purposes: We sought to investigate the incidence, timing, and risk factors for symptomatic epidural hematomas following posterior lumbar decompression, as well as to identify additional post-operative complications associated with symptomatic lumbar epidural hematomas. Methods: Electiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 39 publications
(58 reference statements)
0
30
0
Order By: Relevance
“…In rare cases, such a hematoma may cause critical compression of the thecal sac and result in a SPEH. While the majority of large studies evaluating the incidence of SPEH in the lumbar spine report rates of 0.10%–0.86%,5,7–9,11,17–24 higher incidence ranging from 1.29% to 6.20% has been reported in some recent series 12,13,15,22,25,26…”
Section: Epidemiologymentioning
confidence: 98%
See 2 more Smart Citations
“…In rare cases, such a hematoma may cause critical compression of the thecal sac and result in a SPEH. While the majority of large studies evaluating the incidence of SPEH in the lumbar spine report rates of 0.10%–0.86%,5,7–9,11,17–24 higher incidence ranging from 1.29% to 6.20% has been reported in some recent series 12,13,15,22,25,26…”
Section: Epidemiologymentioning
confidence: 98%
“…Amiri et al19 described a 0.23% incidence of SPEH in a series of 2186 patients undergoing all types of lumbar surgery, with 100% of cases of SPEH occurring in multilevel procedures. A 2019 query of the NSQIP database for all lumbar decompressions noted an OR of 1.70 for surgeries involving 2 or more levels in the setting of overall SPEH incidence of 0.27% 22…”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…For the scope of our review, the definition associated with clinically significant EDH was used. The incidence of clinically significant EDH formation following lumbar spine surgery is reported in the literature to be 0.1% to 0.27% [26,[33][34][35][36]. Risk factors associated with EDH following lumbar spine surgery include the use of gel foam to cover the dura, elevated diastolic blood pressure [32], intraoperative EBL greater than one litre [26,33], history of coagulopathy [35], multilevel operations [26,34,35], older age, longer duration of operation, obesity and repair of torn dura [34].…”
Section: Incidence and Risk Factors Of Postoperative Edhmentioning
confidence: 99%
“…Several studies identified risk factors for development of spinal epidural hematomas, including perioperative transfusion 91 , high intraoperative blood loss (> 1 liter) 98 , pathologic coagulation values, cigarette smoking 97 , intraoperative use of gelfoam for dura coverage, postoperative drain output 100 , increased age, obesity, multilevel surgery, and dural tear repair 102 . Although no studies have specifically investigated anticoagulation use in these high-risk patients, one may want to refrain from administering chemoprophylaxis.…”
Section: - Does the Concern For Epidural Hematoma Influence The Choic...mentioning
confidence: 99%